Para a defesa das Américas: o Herói-Soldado-Cidadão na Revista em Guarda (1941-1945) - Barros, Iberê Moreno Rosário e (2015)
This research analyzes the representation of the american soldiers as an image of the role model to the latin-americans. In this perspective, that the speech presented in the texts and images of the analyzed publication is part of the Good Neighbor Policy, it can be disclosed in the debate around the representation transmited and the internal influences that build it. The investigation arrises from the observation of the 48 editions of Em Guarda, the magazine published between 1941 and 1945, by the Office of the Coordinatior of Inter American Affairs. Starting from a quantitative analysis, in which it was identified the relapses, some of the editions were picked, based on the soldiers thematic, and the texts and imagens were put under a qualitative analysis. Understanding that this soldiers were presented as Heros-Citizen-Soldiers, the work focused on the debate of this concept, from the founding myth of being americans, and as a reference to the image of the cowboy. By this measures, its possible to understand some process and intentions of the americanization of the continent